2022
DOI: 10.1098/rsbl.2022.0110
|View full text |Cite
|
Sign up to set email alerts
|

Artificial light at night reverses monthly foraging pattern under simulated moonlight

Abstract: Mounting evidence shows that artificial light at night (ALAN) alters biological processes across levels of organization, from cells to communities. Yet, the combined impacts of ALAN and natural sources of night-time illumination remain little explored. This is in part due the lack of accurate simulations of the complex changes moonlight intensity, timing and spectra throughout a single night and lunar cycles in laboratory experiments. We custom-built a novel system to simulate natural patterns of moonlight to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 50 publications
(81 reference statements)
0
12
0
Order By: Relevance
“…We fitted incubators for rearing larvae with a unique, custom-built lighting system that simulates ALAN (in the form of LEDs), solar and lunar light cycles (for details see [38]). Briefly, daylight was simulated with an Aquaray Natural Daylight Tile set at 5000 lux diffused with 3 mm frosted Perspex to avoid bright spots [19] and powered by the BioLumen Control Unit (Tropical Marine Centre, UK) timed to match natural variation in sunrise and sunset at Plymouth, UK (50°22'34 00 N, 4°8' 37 00 W).…”
Section: Methods (A) Lighting Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…We fitted incubators for rearing larvae with a unique, custom-built lighting system that simulates ALAN (in the form of LEDs), solar and lunar light cycles (for details see [38]). Briefly, daylight was simulated with an Aquaray Natural Daylight Tile set at 5000 lux diffused with 3 mm frosted Perspex to avoid bright spots [19] and powered by the BioLumen Control Unit (Tropical Marine Centre, UK) timed to match natural variation in sunrise and sunset at Plymouth, UK (50°22'34 00 N, 4°8' 37 00 W).…”
Section: Methods (A) Lighting Setupmentioning
confidence: 99%
“…The datasets supporting this article and code will be uploaded as part of the electronic supplementary material [69].…”
Section: Data Accessibilitymentioning
confidence: 99%
“…Moonlight and starlight can easily be washed out by artificial sources of light, causing shifts in marine biological systems (e.g. Tidau et al, 2022).…”
Section: Natural Marine Light Sourcesmentioning
confidence: 99%
“…Avoidance of light pollution by slow moving marine snails has been reported in the UK (dogwhelks; Nucella lapillus; Underwood et al, 2017) and Chile (large predatory "locos, " Concholepas concholepas; Manríquez et al, 2019). In dogwhelks, light exposure caused a reduction in their response to predator's olfactory cues, and has also been shown to interact with natural moonlight cycles on the foraging rates of this species on acorn barnacles (Tidau et al, 2022). Light pollution also slowed down the ability of locos to up-right their bodies from an upside-down position, a key antipredator ability in this species (Manríquez et al, 2019).…”
Section: Rocky Shores and Related Hard-bottom Speciesmentioning
confidence: 99%
“…Exceptions include a few studies referred above: Orvain and Sauriau (2002) and Garratt et al (2019) found that the effects of light pollution on community biomass and mud snails, respectively, were modulated by the availability of organic matter in the habitat. Similarly, the influence of light pollution on dogwhelk foraging (Tidau et al, 2022) and sea turtle hatchlings (a few studies) interacted with natural moonlight cycles. These studies mark the beginning of the examination of potential synergistical effects (see Halfwerk and Slabbekoorn, 2015) between light pollution and other natural or anthropogenic stressors and should likely escalate in complexity as new research becomes available.…”
Section: Commonalities Gaps Venues and Co-occurring Stressorsmentioning
confidence: 99%